Trademark Protection for MSMEs in Supporting the Creative Digital Economy - Zulfi Chairi; Nurhadi Ahmad Juang; Isdiana Syafitri; Geofani Milthree Saragih; Fabli Yusof (Lex Publica, 2026)
This study examines Indonesia’s legal framework for trademark protection of MSMEs in the creative economy, its implementation in North Sumatra, and necessary policy improvements. Using a mixed-method design qualitative interviews and observations combined with a quantitative Likert-based survey of 204 MSMEs the research analyzes Law No. 20 of 2016 and Law No. 20 of 2008 as normative foundations. Findings show that while Indonesia provides a comprehensive framework, implementation remains weak. Empirical data reveal that 87.2% of MSMEs have not registered trademarks, 6.9% are registered, and 5.9% are in process. Barriers include low legal awareness, complex procedures, weak enforcement, institutional limitations, and technical issues in digital systems. MSMEs that registered trademarks acknowledge their importance for brand protection and market recognition. Strengthening trademark protection requires reforms such as simplified registration, enhanced legal education, institutional coordination, financial incentives, stronger enforcement, and optimized digital platforms.